Urgensi Kebermaknaan Hidup pada Remaja dan Implikasinya dalam Bimbingan Konseling Islam - Ratu Sita Lailatul Ula; Asep Furqonuddin; Yogi Damai Syaputra (DA'WA: Jurnal Bimbingan Penyuluhan & Konseling Islam, 2025)
This study analyzes the urgency of meaning in adolescent life, the strategies used to achieve it, and its implications in Islamic counseling. Unlike previous studies that tend to be general in nature, this study uses data sources obtained from research articles indexed in Google Scholar for the period 2019-2024 with the help of the Harzing's Publish or Perish application. Using the keyword “meaning of life for adolescents,” 140 articles related to the keyword were obtained, which were then analyzed in stages based on the title, abstract, and inclusion-exclusion criteria, resulting in 9 main articles relevant to the research focus. The results of this study indicate that strategies such as forgiveness, self-reflection, Rational Emotive Behavior Therapy (REBT), and existential counseling can be adapted into the Islamic counseling framework. The uniqueness of this study lies in its attempt to connect Viktor Frankl's logotherapy with Islamic values, resulting in a counseling model that is more culturally and religiously relevant to adolescents. This research confirms that meaning in life not only functions as psychological support but also as a spiritual foundation that strengthens adolescents' resilience in facing future pressures and challenges.